The Function of the Power of Attorney Imposes Mortgage Rights in Terms of the provisions of Article 15 of Law Number 4 of 1996 - Mira Novana Ardani (LEGAL BRIEF, 2019)
The granting of credit guarantees should be done directly by the grantor of the mortgage, for something because it can not be present itself, it must appoint the other party as its proxy, with SKMHT in the form of an authentic deed. This research uses empirical / sociological juridical approach. To carry out the SKMHT function, actually any credit agreement is not always made SKMHT. There are legal consequences if after making SKMHT not followed by making APHT